COMPOSITION AND FUNCTIONAL STRUCTURE OF BIRD ASSEMBLAGES IN THREE NATIVE HABITAT REMNANTS IN CENTRAL RIO GRANDE DO SUL STATE, BRAZIL - Sementili-Cardoso, Guilherme [UNESP]; Maffei, Fábio [UNESP]; Donatelli, Reginaldo José [UNESP] (Universidade Federal de Goias, 2023)
The “Uruguayan Savannas” and the “Alto Paraná Atlantic forests” are two dominant ecoregions in the central portion of Rio Grande do Sul state, southern Brazil. However, large areas of these habitats are threatened by anthropogenic activities and require urgent conservation efforts. In order to access the status of bird assemblages in this region, we conducted surveys on three farms located in the central region of Rio Grande do Sul state, Brazil. We aimed to analyze the variation in functional structure (trophic guilds and foraging strata) and species composition within these farms. After 432 hours of transect surveys, we recorded 219 species across the three locations. This finding indicates that these farms host ~31% of the regional bird species pool. Bird community diversity differed among the three farms. Two of the recorded species are threatened with extinction (Hydropsalis anomala (Gould, 1838) and Dromococcyx pavoninus (Pelzeln, 1870), 24 endemics to the Atlantic Forest, and 40 subject to illegal trading. Our data provide evidence that agricultural land holdings can serve as important refuges for birds in this region. Additionally, even areas dominated by forestry activity can maintain relevant biodiversity when associated with conservation practices.
ASSEMBLEIAS DE AVES EM TRÊS REMANESCENTES DE HABITAT NATIVO NA REGIÃO CENTRAL DO ESTADO DO RIO GRANDE DO SUL, BRASIL
Keywords: avian survey; ecotone; hotspot